Microwave-Assisted Synthesis, Optical and Theoretical Characterization of Novel 2-(imidazo[1,5-a]pyridine-1-yl)pyridinium Salts - Luca M. Cavinato; Giorgio Volpi; Elisa Fresta; Claudio Garino; Andrea Fin; Claudia Barolo (Chemistry, 2021)
In the last few years, imidazo[1,5-a]pyridine scaffolds and derivatives have attracted growing attention due to their unique chemical structure and optical behaviors. In this work, a series of pyridylimidazo[1,5-a]pyridine derivatives and their corresponding pyridinium salts were synthesized and their optical properties investigated to evaluate the effect of the quaternization on the optical features both in solution and polymeric matrix. A critical analysis based on the spectroscopic data, chemical structures along with density functional theory calculation is reported to address the best strategies to prevent aggregation and optimize the photophysical properties. The obtained results describe the relationship between chemical structure and optical behaviors, highlighting the role of pendant pyridine. Finally, the presence of a positive charge is fundamental to avoid any possible aggregation process in polymeric films.